Application of GeoGebra software in graph sketching / Norshuhada Samsudin, Fuziatul Norsyiha Ahmad Shukri and Siti Nurleena Abu Mansor - Samsudin, Norshuhada; Ahmad Shukri, Fuziatul Norsyiha; Abu Mansor, Siti Nurleena (Unit Penerbitan JSKM, 2021)
Many studies have shown that information and communication technology (ICT) may help to assist and transform teaching and learning. In mathematics, ICT can assist students and teachers in performing calculations, analyzing data, sketching a graph, and exploring mathematical topics. As a result, it can increase the understanding in mathematics. The purpose of this paper was to show the example of using a free-software called GeoGebra in sketching a graph of two dimensional (2D) and three dimensional (3D) function. Besides sketching the graph, GeoGebra can also be used on finding intersection point, gradient of function, first and second derivatives and others. GeoGebra is an interactive geometry, algebra, statistics, and calculus program designed for learning and teaching mathematics and science at all levels, from elementary to university level.